2008
DOI: 10.7547/0980027
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of the Flexor Digitorum Brevis Tendon

Abstract: Transfer of the flexor digitorum brevis tendon to the dorsum of the proximal phalanx can be performed for correction of claw or hammer toe deformities, especially in the second, third, and fourth toes. The transverse aponeurotic fibers originating from the extensor digitorum longus impede the transfer of the flexor digitorum brevis tendon, and meticulous excision of these fibers is essential to the success of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The long and short flexors were then modelled with bar elements subjected to an initial strain of 2%. This value was calculated by measuring it experimentally in cadavers before and after the flexors were removed (Becerro de Bengoa Vallejo et al, 2008). The whole model consisted of 797,753 elements which were exported to the commercial software package ABAQUS (ABAQUS 6.3, HKS, Providence, RI, USA) where all the simulations were performed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The long and short flexors were then modelled with bar elements subjected to an initial strain of 2%. This value was calculated by measuring it experimentally in cadavers before and after the flexors were removed (Becerro de Bengoa Vallejo et al, 2008). The whole model consisted of 797,753 elements which were exported to the commercial software package ABAQUS (ABAQUS 6.3, HKS, Providence, RI, USA) where all the simulations were performed.…”
Section: Methodsmentioning
confidence: 99%
“…Parrish (1973) was the first one to attempt this latter surgery, performing it in 5 of 23 deformed feet, concluding that the small diameter and insufficient length of the FDB tendon precluded the success of this procedure. More recently, however, Becerro de Bengoa Vallejo et al (2008) performed transposition of the FDB tendon in 64 toes of cadavers, achieving full success, at least purely from the technical point of view, in 63 of them. They found that, despite the firm insertion of the transverse aponeurotic fibers originating from the extensor digitorum longus (EDL) that precluded the transposition of the FDB tendon, an accurate and meticulous resection of these fibers and the flexor sheath permit technical success.…”
Section: Introductionmentioning
confidence: 96%
“…Nathan and Gloobe reported that in 23% of their cases, a part of muscle and tendon inserting the fifth toe was absent, and in 3% of cases inserting in the fourth and fifth toe was absent [9]. Standard descriptions mention that the tendon to the fifth digit is often degenerated or lacking [1,[9][10][11][12]. In addition, Bergmann established that the FDB muscle sometimes has a small fifth tendon which replaces the missing flexor digitorum brevis tendon to the fifth toe [1].…”
Section: Introductionmentioning
confidence: 99%
“…From a clinical perspective, the anatomical variations of FDB reinforce the need to understand anatomical diversity to develop appropriate surgical approaches and diagnostic tools. Awareness of muscle attachments of the foot will assist in biomechanical modeling of the foot and surgical procedures, such as tendon transfer, reconstruction of the heel pad, and correction of claw and hammer toe deformity [6,12].…”
Section: Introductionmentioning
confidence: 99%
“…Percentages of presence of this muscle tendon should be staples of podiatric medical education. Anomalous muscles, bones, or other formations have been documented with certain percentages whereas the lack of the fourth brevis tendon is simply documented as “a known anatomical variation.” 3 The podiatric community would benefit from the knowledge of what percentage of potential patients lack this tendon. It is possible that compensation for the absence of this tendon is achieved by developing extra muscle tone of the other flexors to the fifth toe or that they simply lack that musculature.…”
Section: Introductionmentioning
confidence: 99%